Investigation of factors effecting antibiotics use of health services vocational school students - Tekeli, Hakan; Kiraz, Emre (International Journal Of Community Medicine And Public Health, 2020)
Background: The scope of this study is to evaluate information, behavior and attitude of antibiotics use of students in Golhisar Health Services Vocational School, Burdur Mehmet Akif Ersoy University. Methods: A questionnaire of 19 questions is applied to 701 students. In order to determine students’ attitude at antibiotics use; to evaluate attitude, subjective norm and intention, Likert scale consisting of multiple-choice questions were used. Results: Unattached sample test t showed that there is a significant difference in male and female students in subjective norm effecting antibiotic use and mean points of male students are higher than those of female students. It is found that antibiotic use due to attitude in 20 years and younger students than is significantly higher than 21 years old or older students. No significant difference determined among attitude, subjective norm and intention which effect use of antibiotics in terms of alcohol use, chronic disease and health insurance possession. As the programs that students are attending are evaluated, difference is observed only in attitude factor in this study. It is determined that attitude to antibiotic use of students of first and emergency aid program is lower than pharmacy services and child development programs. Conclusions: This study has shown that students are conscious about antibiotics use and their level of antibiotics use is low. Based on the results of the study, having individuals in the society educated about antibiotics use will substantially contribute to conscious use of antibiotics.